ANALISIS RESPON SISWA TERHADAP PENGGUNAAN KIT MATEMATIKA PADA PEMBELAJARAN KURMER SEKOLAH DASAR - Fitriyani, Fitriyani; Khoiri, Ahmad (FKIP UM Pontianak, 2026)
This study aims to determine the response of fourth-grade students to the use of mathematics kits in learning within the Merdeka Curriculum. The research employed a Mixed Methods approach with a Sequential Explanatory Design, which begins with quantitative data collection followed by qualitative data to provide deeper explanations of the results. The subjects of this study were 23 fourth-grade students at SDN 25 Tahalut. Data were collected through student response questionnaires, observations, and interviews. The questionnaire used a Likert scale ranging from 1 to 4. Quantitative data were analyzed using descriptive statistics including mean, median, and mode, while qualitative data were analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The results showed that students’ responses to the use of mathematics kits were in the very good category, with a mean score of 84.61, a median of 85, and modes of 84 and 85. After being converted to a Likert scale, the average score was 3.38, which falls into the very good category. Observations and interviews also indicated that the use of mathematics kits increased students’ activeness, attention, and enthusiasm during mathematics learning. Therefore, mathematics kits can serve as an effective learning medium to help students understand mathematical concepts more concretely and create a more engaging and interactive learning environment.